Use of investigative activity elements in criminal proceedings - Slinko, D. S. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
Article deals with the elements of the criminal procedure form in criminal proceedings and using the OSA results. Has been given the theoretical model of using elements of operatively-searching activity in criminal proceedings. The theoretical and practical problems of procedural form of criminal justice are considered by implementing a mechanism of drawing up procedural resolution. Based on the results of the analysis proposals on the improvement of the current Ukrainian legislation and its implementation have been given.